Waste to health: organic waste management for sustainable soil management & crop production - Abu Bakar, Rosenani (Universiti Putra Malaysia Press, 2014)
Organic waste management is essential not only in turning waste into wealth but more importantly in improving environmental quality and health, and contributing to sustainable crop production when it is recycled in the agricultural sector. The agricultural sector in Malaysia produces a tremendous amount of waste which has traditionally been burnt or simply dumped (a common practice till now) making it a source of greenhouse gas emissions and other environmental problems which affect human health. More recently, due to the prohibition of open burning of organic wastes, it has become a trend to convert wastes into wealth, i.e. value added products. Research has escalated to investigate various technologies with the aim of reducing waste through good waste management practices, i.e. recycling in agriculture or conversion into useful products for commercialization. However, returning organic wastes back to agricultural land simply by mulching(e.g. oil palm empty fruit bunches (EFB) applied fresh from the mill or as processed EFB mats to newly transplanted palms and mature palms) or incorporation of crop residues into soils after harvesting contributes to recycling of nutrients and organic matter back into soils, thus building up soil quality and health, prevents land degradation and increases soil productivity. Composting of organic wastes (not limited to agricultural wastes) reduces the bulk of the wastes and concentrates nutrient contents. This process not only converts the wastes into value-added products such as organic fertilizers, soil amendments and soilless potting media but also avoids wastes being exposed to the environment and vulnerable to greenhouse gas emissions (nitrous oxide and methane) and pollution of natural resources (leaching into groundwater and surface run-off into surface waters). The use of soilless potting media derived from organic wastes could partially or totally replace the use of peat which is a slowly renewable resource.Apart from this, there has been an increase in interest, in the last decade, in transforming organic wastes into biological charcoal or biochar under controlled conditions, such as pyrolysis and gasification, with the main objective of using it as a soil amendment in agricultural land, particularly for naturally infertile or degraded soils. Biochar contains carbon that is potentially resistant to microbial degradation and has dual functions. Firstly, biochar improves soil quality and crop productivity due to its high porosity and sorption properties. Secondly, biochar increases carbon storage or sequestration in soil thus reducing carbon dioxide in the atmosphere and mitigating global warming and climate change. Sustainable management and recycling of organic wastes in agriculture is a holistic approach which should be pursued not only with the sole objective of converting wastes into wealth but more seriously for its various benefits to crop production, the environment (clean water and air, and balanced carbon cycle) and, ultimately, human health.